2008
DOI: 10.1089/ees.2007.0137
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Characterization of Aerosol Sediments Formed by Plasma-Induced CS2 Destruction Processes

Abstract: Removal of odorous carbon disulfide (CS 2 ) can be carried out via destructing into solid aerosols and gaseous products by using a radiofrequency (rf) discharge approach. A large amount of depositions at the glow discharge zone as well as traces of plasma-polymerized films at the afterglow discharge zone was formed. The structures of the aerosol sediments were identified in this study. The composition analysis showed that at inlet O 2 /CS 2 ratio (R) ϭ 0.6, elemental sulfur with an S 8 structure was the domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Their results corroborated the primary dissociation steps of OCS reported by previous authors, and showed that the main dissociation pathway for CS 2 should be e − + CS 2 → CS + S + e − . More recent studies on CS 2 plasmas have been devoted to their application as sources of functional polymers (Ochiai & Endo 2005, and references therein) or as a method for CS 2 waste removal (Holub et al 2014; Yan et al 2013; Tsai et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Their results corroborated the primary dissociation steps of OCS reported by previous authors, and showed that the main dissociation pathway for CS 2 should be e − + CS 2 → CS + S + e − . More recent studies on CS 2 plasmas have been devoted to their application as sources of functional polymers (Ochiai & Endo 2005, and references therein) or as a method for CS 2 waste removal (Holub et al 2014; Yan et al 2013; Tsai et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The rest is from combustion of fossil fuels, volcanic eruptions, and plant or protein corruption (8–21%). , CS 2 can serve as a solvent for bromine, iodine, fats, phosphorus, sulfur, selenium, resins, rubber, and asphalt. In addition, CS 2 is a known chemical industry raw material and highly volatile compound, and it is listed as a dangerous air pollutant by many countries. In general, CS 2 is regarded as a poison that is hard to ignore for industrial catalysis because its presence can cause catalyst deactivation and corrosion of reaction equipment. Moreover, CS 2 not only causes economic problems but also affects the environment because its pollution can cause major damage to the natural world. , In fact, the CS 2 molecule is recognized to be a main pollutant in the atmosphere. , For example, CS 2 can be oxidized by atmospheric oxygen through photochemical reactions to form sulfur oxide, which has been proven to be the main source of acid rain. Consequently, many methods have been developed to remove CS 2 from tail gas and other processed gas streams. …”
Section: Introductionmentioning
confidence: 99%